Efektivitas Videography dengan Menggunakan Powtoon untuk Meningkatkan Pemahaman Mengenai Bullying - Dominikus David Biondi Situmorang; Kusumasari Kartika Hima Damayanti; Haleda Riezka Hairunnisa Ns (Indonesian Journal of Learning Education and Counseling, 2020)
Abstract. Background: Data from KPAI indicates that there is a high number of perpetrators and victims of bullying. On the other hand, bullying impacts on physical and mental health risks. Especially in line with the development of communication systems, interaction and communication on digital platforms increasingly out of control. The research aims to examine the effectiveness of videography related to bullying material to increase the understanding of bullying. Methods: Data from participants (N = 4) involved in the study were processed qualitatively, including differences in the understanding of participants when before and after the provision of material through videography. Results: Qualitatively, there was an increase in understanding of bullying by using videography. Discussion: Videography based learning always connects to learning spaces and zones, reflection for action (before action), reflection in action (during an action), and reflection of action (after action) consist of the role of reflection and action in learning. Conclusion: The use of videography with Powtoon is effective in increasing understanding of bullying. Implication: For Educators, trainers, and presenters, the use of videography with Powtoon can be applied as a medium in learning and teaching. Abstrak. Latar belakang: Data dari KPAI mengindikasikan bahwa terdapat jumlah pelaku dan korban bullying yang cukup tinggi. Di sisi lain, bullying berdampak pada resiko kesehatan fisik dan kesehatan mental. Terlebih sejalan dengan berkembangnya sistem komunikasi, interaksi dan komunikasi pada platform digital semakin tidak terkendali. Penelitian bertujuan untuk menguji efektivitas videography terkait materi bullying terhadap peningkatan pemahaman bullying. Metode: Data dari partisipan (N = 4) yang terlibat pada penelitian diolah secara kualitatif, meliputi perbedaan pemahaman partisipan ketika sebelum dan sesudah pemberian materi melalui videography. Hasil: Secara kualitatif, terdapat peningkatan pemahaman bullying dengan menggunakan videography. Diskusi: Pembelajaran berbasis videography selalu menghubungkan ke ruang dan zona belajar, refleksi untuk tindakan (sebelum tindakan), refleksi dalam tindakan (selama aksi), dan refleksi tindakan (setelah tindakan) terdiri dari peran refleksi dan tindakan dalam pembelajaran. Kesimpulan: Penggunaan videography dengan Powtoon efektif dalam meningkatkan pemahaman bullying. Implikasi: Bagi Pendidik, pelatih, dan pemateri, penggunaan videography dengan Powtoon bisa diterapkan sebagai media dalam belajar dan mengajar.